Land grabbing on Brazil's Highway BR-319 as a spearhead for Amazonian deforestation. (September 2021) - Ferrante, Lucas; Andrade, Maryane B.T.; Fearnside, Philip M.
Abstract: Brazil faces its greatest period of environmental setback, where "ruralists" (large landholders and their representatives) gain access to government land in the Amazon. New roads are being paved, such as Highway BR-319 connecting Porto Velho in Brazil's notorious "arc of deforestation" to Manaus in relatively intact central Amazônia. This highway acts as a spearhead penetrating one of the Amazon's most preserved forest blocks. Here we report how the Brazilian government has been favoring land grabbing ( grilagem ) in the Amazon and how BR-319 has given access to public lands and encouraged the invasion of these areas together with land grabbing and deforestation. This is not just a process linked to the highway, as it also involves the actions of government agencies such as the National Institute for Colonization and Agrarian Reform (INCRA). Illegal logging is rampant and areas of government land are being marked out by land grabbers ( grileiros ) for illegal sale to arriving migrants. Despite environmental legislation requiring an environmental impact assessment (EIA) for "Lot C, " which is one of stretches where deforestation is advancing, a judge has authorized paving this stretch without an EIA. Opening BR-319 and its associated side roads represents a path with no return to a tipping point of self-degradation and loss of Amazonia's vital biodiversity and climate-stabilization functions. Highlights: Brazil's planned reopening of Highway BR-319 is increasing Amazonian land grabbing. BR-319 and planned side roads would bring conflicts from the "arc of deforestation". Vast areas of unclaimed government land would be opened to entry of land-grabbers. Deforestation in the area to be opened would have consequences for global climate. Land grabbing was observed along BR-319 as well as titling of illegal claims.